2020
DOI: 10.7150/jca.36919
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Carboplatinum- and Taxol-Resistant High-Grade Serous Ovarian Cancer Cells Carrying p53, BRCA1/2 Mutations by Emblica officinalis (Amla) via Multiple Targets

Abstract: Background: Ovarian cancer (OC), the most lethal gynecologic malignancy, is highly resistant to current treatment strategies. High-grade serous epithelial ovarian cancer (HGSOC) cells with increased somatic mutations and genomic instability and the resulting heterogeneous mutant phenotypes are highly resistant to therapy. Plant-derived natural products, including Amla (Emblica officinalis) extract (AE), have demonstrated potent anti-neoplastic properties. Recently we demonstrated that AE inhibits cell growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…34 De et al also found that the apoptotic genes are expressed significantly after taxol administration. 35 In the current study, thymoquinone reduced apoptotic cell index and apoptotic gene expression to prevent cell death. Based on the obtained results, it can be indicated that thymoquinone owns positive antioxidant effects on molecular function and histological construction of liver cells.…”
Section: Discussionmentioning
confidence: 53%
“…34 De et al also found that the apoptotic genes are expressed significantly after taxol administration. 35 In the current study, thymoquinone reduced apoptotic cell index and apoptotic gene expression to prevent cell death. Based on the obtained results, it can be indicated that thymoquinone owns positive antioxidant effects on molecular function and histological construction of liver cells.…”
Section: Discussionmentioning
confidence: 53%
“…15 . The current standard treatment for advanced ovarian cancer is cytoreductive surgery and platinum/taxane-based chemotherapy [16][17][18] . The response rate to treatment is approximately 80-90%, but many often relapse and develop resistance to chemotherapy 14 .…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…The pre-clinical experiments of various cancer cell lines (A549 [lung], HepG2 [liver], HeLa [cervix], MDA-MB-231 [breast], SK-OV-3 [ovary] and SW620 [colorectal]) showed that the water extracts of PF (50–100 μg/ml) can induce apoptosis by activating caspase-8 and caspase-3/7 and upregulating Fas expression ( Ngamkitidechakul et al, 2010 ). PF extracts also sensitized refractory high-grade serous ovarian cancer (HGSOC) cells with high drug resistance by regulating key signalling molecules of angiogenesis and metastasis ( De et al, 2020 ).…”
Section: Pharmacological Effects Of Phyllanthi Fructusmentioning
confidence: 99%